A novel PAX6 variant as the cause of aniridia in a Chinese patient with SRRRD - Qian Wang; Wen Bin Wei; Xiang Yu Shi; Wei Ning Rong (BMC, 2023)
Abstract Background The genotype characteristics and their associated clinical phenotypes in patients with aniridia were analyzed to explore pathogenic variants using whole-exome sequencing. Methods One patient with aniridia was enrolled at the Beijing Tongren Hospital. Comprehensive ophthalmic and general examinations were performed on the patient. DNA was extracted from the patient, and whole-exome sequencing was performed to identify the causative variant. The pathogenicity of the variant was predicted using in silico analysis and evaluated according to American College of Medical Genetics and Genomics guidelines. Relationships between genetic variants and clinical features were analyzed. Results In addition to the classical aniridia phenotype showing complete iris aplasia, foveal hypoplasia, and ectopic lentis, the patient also exhibited spontaneous reattachment rhegmatogenous retinal detachment (SRRRD). Whole-exome sequencing identified a novel heterozygous variant, exon8:c.640_646del:p.R214Pfs*28. Conclusions The present study broadens the range of genetic variants described in aniridia and presents an aniridia patient with SRRRD.